Functional Analysis: Definition and Application in Behavior-Analytic Therapy (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
This paper reviews some uses of the concept of functional analysis in behavior analysis and behavior therapy, emphasizing its relation to the causal mode of selection by consequences. It proposes that a clinical application of functional analysis consistent with the behavior-analytic explanatory system would be based on: a) selectionism as a causal model and functionalism as the principle for analysis; b) externalism as analytical orientation; c) the complexity, variability, and idiosyncrasy of behavioral relations; d) the pragmatic criteria for defining the intervention level; e) the distinction between assessment scope and intervention scope.